Challenges for Nurses Caring for Individuals with Peripherally Inserted Central Catheters in Skilled Nursing Facilities. Issue 10 (7th September 2016) - Harrod, Molly; Montoya, Ana; Mody, Lona; McGuirk, Helen; Winter, Suzanne; Chopra, Vineet
Abstract : Objectives: To understand the perceived preparedness of frontline nurses (registered nurses (RNs), licensed practical nurses (LPNs)), unit nurse managers, and skilled nursing facility (SNF) administrators in providing care for residents with peripherally inserted central catheters (PICCs) in SNFs. Design: Exploratory, qualitative pilot study. Setting: Two community based SNFs. Participants: Residents with PICCs, frontline nurses (RNs, LPNs), unit nurse managers, and SNF administrators. Methods: Over 36 weeks, 56 residents with PICCs and their nurses were observed and informally interviewed, focusing on PICC care practices and documentation. In addition, baseline PICC data were collected on placement indication (e.g., antimicrobial administration), placement setting (hospital vs SNF), and dwell time. Focus groups were then conducted with frontline nurses and unit nurse managers, and semistructured interviews were conducted with SNF administrators to evaluate perceived preparedness for PICC care. Data were analyzed using a descriptive analysis approach. Results: Variations in documentation were observed during weekly informal interviews and observations. Differences were noted between resident self‐reported PICC concerns (quality of life) and those described by frontline nurses. Deficiencies in communication between hospitals and SNFs with respect to device care, date of last dressing change, and PICC removal time were also noted. During focus group sessions, perceived inadequacy of information at the time of care transitions, limited availability of resources to care for PICCs, and gaps in training and education were highlighted as barriers to improving practice and safety. Conclusion: Practices for PICC care in SNFs can be improved. Multimodal strategies that enhance staff education, improve information exchange during care transitions, and increase resource availability in SNFs appear necessary to enhance PICC care and safety.